Genetic Diversity of Whiteflies Colonizing Crops and Their Associated Endosymbionts in Three Agroecological Zones of Cameroon - Lanvin R. K. Kepngop; Everlyne N. Wosula; Massoud Amour; Pierre G. T. Ghomsi; Louise N. Wakam; Germain Kansci; James P. Legg (Insects)
Bemisia tabaci (Gennadius) is as a major pest of vegetable crops in Cameroon. These sap-sucking insects are the main vector of many viruses infecting plants, and several cryptic species have developed resistance against insecticides. Nevertheless, there is very little information about whitefly species on vegetable crops and the endosymbionts that infect them in Cameroon. Here, we investigated the genetic diversity of whiteflies and their frequency of infection by endosymbionts in Cameroon. Ninety-two whitefly samples were collected and characterized using mitochondrial cytochrome oxidase I (mtCOI) markers and Kompetitive Allele Specific PCR (KASP). The analysis of mtCOI sequences of whiteflies indicated the presence of six cryptic species (mitotypes) of Bemisia tabaci, and two distinct clades of Bemisia afer and Trialeurodes vaporariorum. Bemisia tabaci mitotypes identified included: MED on tomato, pepper, okra, and melon; and SSA1-SG1, SSA1-SG2, SSA1-SG5, SSA3, and SSA4 on cassava. The MED mitotype predominated in all regions on the solanaceous crops, suggesting that MED is probably the main phytovirus vector in Cameroonian vegetable cropping systems. The more diverse cassava-colonizing B. tabaci were split into three haplogroups (SNP-based grouping) including SSA-WA, SSA4, and SSA-ECA using KASP genotyping. This is the first time that SSA-ECA has been reported in Cameroon. This haplogroup is predominant in regions currently affected by the severe cassava mosaic virus disease (CMD) and cassava brown streak virus disease (CBSD) pandemics. Three endosymbionts including Arsenophonus, Rickettsia, and Wolbachia were present in female whiteflies tested in this study with varying frequency. Arsenophonus, which has been shown to influence the adaptability of whiteflies, was more frequent in the MED mitotype (75%). Cardinium and Hamiltonella were absent in all whitefly samples. These findings add to the knowledge on the diversity of whiteflies and their associated endosymbionts, which, when combined, influence virus epidemics and responses to whitefly control measures, especially insecticides.